12 - Review Article: The Frontier of Interculturality. A Review of Wim van Binsbergen's Intercultural Encounters: African and Anthropological Lessons towards a Philosophy of Interculturality (2003), Münster: Lit Verlag, 610 pages 40.90 Euros. - Osha, sanya (Africa Development, 2005)
Abstract